O desenho como processo de aprendizagem da criança na educação infantil - Assis, Suzy Daiana Tavares (Brasil, 2024)
This Course Completion Work - TCC, aims to understand how drawing is used in classes of I and II period of Early Childhood Education, in two Children's Educational Centers - CEI, of the municipal network of Parintins, in the Lower Amazon. It is observed how it helps the teacher in the classroom, seeking to relate drawing with the child's development, be it cognitive, motor, social, as a means of communication and what contributions it brings to child development. In the first moment of the research, a bibliographic survey was carried out, where different views were sought in relation to the researched theme, and it has a qualitative approach, in order to allow a more attentive and careful look at the proposed theme. Then, a field research was carried out with observation in the classroom during the period of development of the discipline of Supervised Internship I Early Childhood Education and later during the Pedagogical Residency Program. From what was observed, we can see that drawing is essential in the educational field for children, as it can and should be used as a method of learning and development of the child.